National legislation is in the field of extracharge of salary - Trufanova, Yulia; Verba, Tetiana (Actual problems of law (Aktual’ni problemi pravoznavstva), 2018)
The article is devoted to the consideration of issues in the area of wage calculation, the legal regulation of the basic acts defining the structure of wages and the main conditions for its payment. Considering the positions of scientists, the article gives a modern understanding of the concept of «wages» as legal on the one hand and socioeconomic from another category. The article deals with the basic law regulating relations in the field of accrual and payment of wages, provided the concept of «wages» within the framework of the considered Law of Ukraine «On Labor Remuneration». The study shows a separate procedure for the assessment of judges’ remuneration, which is governed by the norms of the aforementioned law